Clinical Profile of Indian Children with Down Syndrome - Panigrahi, Inusha; Bhatt, Yogita; Malik, Shivani; Kaur, Parminder; Kaur, Anupriya (Journal of Pediatric Genetics, 2021)
This retrospective study was performed on 208 patients with Down syndrome (DS) from heterogeneous ethnic population and admitted under Genetics Metabolic Unit. The aim of the study was to look for phenotypic variability and associated complications in children and adolescents with DS. The average age of the evaluated DS patients was 34 months. Cardiac anomalies were found in 128 (62%) of the 208 cases. Among the cardiac disorders, atrial septal defects accounted for 30% of cases. Other complications observed were hypothyroidism and developmental delay in around 31% cases and neonatal cholestasis in 14% cases. Also, we report two cases with Moya-Moya disease and one case with atlanto-axial dislocation.
Keywords: aneuploidy; atrioventricular septal defect; double aneuploidy; karyotyping; trisomy 21